The Capital Market Consequences of Tenure-Based Voting Rights: Evidence from the Florange Act - Bourveau, Thomas; Brochet, François; Garel, Alexandre (Management Science, 2022)
We examine the consequences of a regulatory intervention aimed at generalizing tenure voting in French public companies. The 2014 Florange Act departs from the ‘one share one vote’ principle by automatically granting double-voting rights (DVR) to shares held for at least two years. However, firms can opt out through an annual meeting vote. We document three main findings. First, firms that adopt DVR by default experience a decrease in long-term foreign institutional ownership offset by an increase in insider/family ownership. Second, those firms significantly underperform in terms of stock returns after Florange relative to those that reject DVR. Third, their environmental and social performance deteriorates. Collectively, our evidence casts doubt on the merit of regulation-induced tenure voting as a desirable corporate governance mechanism. This paper was accepted by Brian Bushee, accounting. Funding: This work was supported by Research Grants Council of Hong Kong [16513216]. We also acknowledge the General Research Fund of the Research Grants Council of Hong Kong [Project No. 16505017] for financial support. Supplemental Material: The e-companion and data are available at https://doi.org/10.1287/mnsc.2022.4320 .